(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the research of the social-crime motives in activity of Zaporozian-Haydamaks during the XVIII age. Materials of the Poland, Russian Federation and Ukraine archives, which were brought into the scientific turn firstly, are the basis for the scientific research.